Everyman og Superman. Litterære og videnskabelige narrativer i G. B. Shaws “Man and Superman” og i “The Science of Life” af H.G. Wells, Julian Huxley og G. P. Wells - Thomasen, Laura Søvsø (Passage - Tidsskrift for litteratur og kritik, 2018)
Laura Søvsø Thomasen: “Everyman og Superman. Literary and Scientific Narratives in G. B. Shaw’s Man and Superman and in The Science of Life by H.G. Wells, Julian Huxley og G.P. Wells” In G. B. Shaw’s 1902-play “Man and Superman” a new stage of human evolution is envisioned. Shaw’s superman was presented not as the next step of the Darwinian evolution, but rather as a view of the new human as a pure philosophical creature almost without a body. Some of the ideas Shaw presented in his play are also visible in other contemporary works of science and fiction, like the popular scientific work The Science of Life (1929-30) by H. G. Wells, Julian Huxley and P. G. Wells. In the Thomasen discusses how the view of the new human is a culmination of a grand narrative that challenges aspects of Darwin’s evolutionary narrative, while at the same time placing the human in a context pointing back to the medieval trope of the ‘Everyman’-figure.